How do sustainability standards consider biodiversity?. Issue 1 (20th March 2014) - Englund, Oskar; Berndes, Göran
<x xml:space="preserve">Abstract</x> Sustainability certification schemes and standards are meant to prevent a range of unacceptable socioeconomic and environmental consequences, such as threats to biodiversity. While there is wide support for conserving biodiversity, operationalizing this support in the form of guiding principles, criteria/indicators, and legislation is complicated. This study investigates how and to what extent 26 sustainability standards (eleven for forest management, nine for agriculture and six biofuel‐related) consider biodiversity, by assessing how they seek to prevent actions that can threaten biodiversity as well as how they support actions aimed at biodiversity conservation. For this purpose, a benchmark standard was developed, meant to represent a case with very high ambitions concerning biodiversity conservation. Of the assessed standards, the biofuel‐related standards demonstrated the highest level of compliance with the benchmark. On average, they complied with 72% of the benchmark's component criteria, compared to 61% for the agricultural standards and 60% for the forestry standards. Fairtrade, Sustainable Agriculture Network/Rainforest Alliance (SAN/RA), Roundtable on Sustainable Palm Oil (RSPO), and Roundtable on Responsible Soy (RTRS) were particularly stringent, while Green Gold Label S5 (GGLS5), PEOLG, Global Partnership for Good Agricultural Practices (GLOBALGAP), European Union Organic (EU Organic), National Organic Program (NOP), Green Gold Label S2 (GGLS2), and International Sustainability & Carbon Certification (ISCC) were particularly unstringent. All eleven forestry standards, six of the nine agricultural standards, and all six biofuel‐related standards addressed ecosystem conversion, ranging from requiring that high conservation value areas be identified and preserved to requiring full protection. Finally, key barriers to, and challenges for, certification schemes are discussed and recommendations are made for further development of sustainability standards. WIREs Energy Environ 2015, 4:26–50. doi: 10.1002/wene.118 For further resources related to this article, please visit the WIREs website. Conflict of interest: The authors have declared no conflicts of interest for this article.